Analisis Fungsi Informed consent Terhadap Tindakan Medis Poli gigi di Puskesmas Kebumen 1 - Kukuh Saksono; Puji Lestari; Syaikhul Wahab (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Dental poly health services in filling out the informed consent form, there is an action where an action requires agreement between the doctor and patient to maintain the convenience and safety of both parties, basically the informed consent function that I take refers more to doctors, dental nurses, and the patients themselves because there are still mistakes in filling out the medical action approval sheet. The purpose of this study is the function of informed consent for dental polyclinic medical action. This type of research method uses a descriptive method with a qualitative approach, while for data collection techniques, the study takes data by observation and interviews, based on the results of the study, 76.7% of complete data were obtained while 23.3% were incomplete from a total sample of 30 forms. informed consent. The problem factors are the completeness of filling out the medical action approval form at the dental poly, the limited time in filling it out, the number of patients.